Global Impact of Patchwork Weaving on Children's Concentration: Dampak Global Tenun Kain Perca terhadap Konsentrasi Anak - Laila, Tabi’ina Nikmatul; Salim, Agus (Indonesian Journal of Education Methods Development, 2024)
This study investigates the effectiveness of patchwork weaving activities in enhancing children's concentration during learning at TK A'isyiyah Bustanul Athfal 1 Kemantren. Using the Classroom Action Research model by Kemmis and Mc. Taggart, twelve children participated in two cycles of patchwork weaving sessions, with the second cycle involving independent work. Results show a significant increase in children's concentration from Cycle I to Cycle II, indicating the effectiveness of patchwork weaving in improving their focus and engagement during learning activities. These findings suggest that incorporating patchwork weaving into early childhood education could contribute to better learning experiences and cognitive development for young children. Hightligh: Engagement: Patchwork enhances learning engagement. Independence: Children work independently. Cognitive Growth: Concentration improves cognitive development. Keywords: Patchwork weaving, Concentration, Early childhood education, Classroom Action Research, Cognitive development